Octávio Ianni: da metamorfose do povo à democracia popular - Brito, Jeanne Gomes de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
This article analyses the Octávio lanni's intellectual trajectory, specially the period that Ianni stayed on Faculdade de Ciências e Letras da USP (decade 1950 until 1969), in order to analyzer the studies of UNESCO; the "Capital group"; the works around CESIT and vour partnership in Revista Civilização Brasileira. Then, we situate the discussion about democracy whose presence is in others themarics, organized by Ianni, like the ethnic question; the relation between State and society; and the themes with regard to working class.